Analysis Implementation of the Gold Pawn at Sharia Bank and Sharia Pawnshop Abu Syuja’s Perspective - rizky andrean; muhammad aris safi'i (Jurnal Ilmiah Ekonomi Islam, 2022)
Pawn gold is a financial service product that is an alternative for the public to get funds. For a Muslim, a good gold pawn is sharia-compliant where this is possible in Islamic financial institutions. This study aims to determine the implementation of pawning gold in Islamic Banks and Sharia Pawnshops based on Abu Syuja's perspective as stated in his work, namely Matan Ghayah wa Taqrib (Kitab Fathul Qarib). This study uses a qualitative approach, with field data and literature analysis as supporting data. The primary data used in this study is data that describes the practice of pawning Islamic gold in Islamic banks and Islamic pawnshops. The secondary data used is derived from various theoretical literatures and previous research that is used to support the analysis of this research study. The results of the study indicate that the implementation of the gold pawn in Islamic banks and Islamic pawnshops is based on the rahn contract as one of the foundations of the contract. There has been a match between the implementation of the gold pawn in Islamic banks and the sharia pawnshop with the pillars and conditions of rahn according to Abu Syuja's perspective. In gold pawning, rahin is a customer who pawns his gold to obtain a certain amount of funds. Murtahin is a Sharia Bank or Sharia Pawnshop. Marhun is gold in the form of gold bars, jewelry, and dinar coins. Marhun bih is the amount of funds obtained by rahin from the murtahin. The ijab qabul is a contract agreement that marks the occurrence of a gold pawn transaction between rahin and murtahin. All the pillars of the pawn exist and have been fulfilled in the implementation of the gold pawn in the Islamic Bank and in the Sharia Pawnshop.